Improving junior high school students' vocabulary understanding by using quiz-based application - Azhra, Shabrina Yumna; Carabella, Primita Arif; Eiden, Kheisen; Payung, Naftalia Fany; Sukarno, Sukarno; Pratiwi, Dwiyani; Gharamah, Fadhl Mohammed Awadh (Diksi, 2024)
This study aims to improve the students' vocabulary through quiz-based application. Therefore, the problems that students have are lack of vocabulary skills and distraction from their gadgets. This paper also gives alternative options for teachers who teach 7th grade in junior high school to using quiz-based applications to increase students' interest in vocabulary skills. The method used in this study is Classroom Action Research (CAR) with 29 participants. The instrument used a questionnaire and test to ensure students' vocabulary skills. As mentioned before, students had a lack of understanding of vocabulary and distractions from their gadgets. The effects of quiz-based programs, especially Quizlet, on seventh-grade students' vocabulary knowledge are apparent from both a quantitative and qualitative standpoint. The benefits seen in test results and student participation show how successful it is to include technology-driven tools into language instruction. However, this study has limitations that can be used for next other researchers. It is advised that educational institutions and technology developers continue to work together to guarantee that quiz-based solutions are continuously improved and customized to fit the changing demands of instructors and students